Features of the lactate dehydrogenase isoenzymes spectrum in animal tissues and organs - Kuzmina, N. V.; Ostapiv, R. D.; Ostapiv, D. D.; Golovach, P. I. (Regulatory Mechanisms in Biosystems, 2024)
Activity and content of lactate dehydrogenase (LDH) isoenzymes is one of the objective criteria for assessing oxidative metabolism in organs and tissues and the physiological state of the whole organism. Lactate dehydrogenase (LDH) is a key enzyme of energy metabolism. LDH is a heterotetrameric protein consisting of subunits of two types H (cardiac) and M (muscular). This enzyme exists in five isoforms: LDH1, LDH2, LDH3, LDH4 and LDH5. Each of the isoforms is characterized by different physicochemical and catalytic properties and is found in most tissue cells. Content of LDH isoenzymes is not constant and depends on the intensity of oxidative metabolism in tissue cells and on the influence of various factors, including new therapeutic drugs and biogenic compounds. Therefore, the aim of the research was to study and establish the limits of isoenzyme content and LDH activity in individual tissues and organs of rats, pigs and cows to characterize and detect changes in the intensity of metabolism in the body of the animals under different physiological state. Tissue samples of rat, pig and cow organs were taken for research. Isoenzymes of lactate dehydrogenase were detected by staining according to Garbus in our modification. The content of isoenzymes (%) was determined by the TotalLab TL120 software, the activity of LDH in blood plasma (µkat/L) and in tissue homogenates (µkat/mg protein) – by the rate of NADH oxidation. Brain, spleen, liver, kidney, testis, muscle and blood plasma of rats and pigs were characterized by 5 catalytically active LDH isoenzymes. In muscle and liver tissues, LDH5 prevailed, and in the brain, testis and kidney – LDH1. LDH3 was most abundant isoenzyme in spleen tissue. It was found that the same activity of LDH in the tissues of the liver and testis of rats (lim 4.5–4.6 µkat/mg of protein) was provided by different LDH isoenzymes. In addition to tissue characteristics, the content of LDH isoenzymes depended on the physiological state of the organ. Thus, in the cow ovaries the activity of LDH was the same (2.8–3.0 µkat/mg of protein) under the physiological state of "follicular growth" and pathology – "hypofunction". LDH activity was lower by 0.6 and 1.0 µkat/mg of protein under "early" and "late" corpus luteum (2.0 and 2.2 µkat/mg of protein). The highest content of LDH1 was in the physiological state of "late corpus luteum", and LDH3, LDH4 and LDH5 – in "early corpus luteum". Content of LDH2 was high in the state of ovarian dysfunction – "hypofunction". Content of LDH2 was lower and had no statistical difference (19.8% and 22.1%) in other physiological states. Isoenzyme spectrum of LDH was characterized by tissue specificity. Tissues with a predominance of anaerobic processes (muscle and liver) were characterized by a high content of LDH5, and with a predominance of aerobic processes (brain, testis, kidneys) – by a high content of LDH1. The spleen was characterized by a high content of LDH3. It was established, that the same activity of the enzyme in the organs could be ensured by different content of LDH proteins. It has been proven that the content of individual LDH isoenzymes depended on the physiological state of the ovary.